Developing intercalation based anode materials for fluoride-ion batteries: topochemical reduction of Sr2TiO3F2via a hydride based defluorination process. Issue 44 (24th May 2018) - Wissel, Kerstin; Dasgupta, Supratik; Benes, Alexander; Schoch, Roland; Bauer, Matthias; Witte, Ralf; Fortes, Andrew Dominic; Erdem, Emre; Rohrer, Jochen; Clemens, Oliver
Abstract : Sr2 TiO3 F2− x, a potential anode material for fluoride ion batteries, is prepared in the charged state via selective low-temperature defluorination. Abstract : Within this study, we demonstrate a newly developed reductive topochemical defluorination method which allows for a selective extraction/substitution of fluoride ions out of transition metal oxyfluorides using NaH as the reducing agent at temperatures as low as 300 °C, enabling the preparation and investigation of anode materials for fluoride-ion batteries in the charged state. A sequence of topochemical reactions, first substitutive fluorination of the K2 NiF4 type precursor oxide Sr2 TiO4 to Sr2 TiO3 F2 followed by the reductive defluorination/hydride-fluoride-substitution of Sr2 TiO3 F2, leads to the formation of compounds with approximate compositions of Sr2 TiO3 FH0.48 and Sr2 TiO3 H1.48 . The evolution of the unit cell volumes upon extraction/substitution of fluoride ions has been monitored by an X-ray diffraction study. Strong structural changes were observed during the reaction, expressed by a decrease of the c -axis from ∼15.5 Å in Sr2 TiO3 F2 to ∼13.0 Å in Sr2 TiO3 FH0.48 and ∼12.7 Å in Sr2 TiO3 H1.48, with additional symmetry lowering for Sr2 TiO3 FH0.48, and confirmed by neutron powder diffraction. Changes of the Ti oxidation states and coordination environment were examined and confirmed by means of X-ray absorption spectroscopy, electron paramagnetic resonance and magnetic measurements. Furthermore, we found that the surface chemistry of such compounds differs significantly from the bulk properties by means of an X-ray photoelectron spectroscopy study, showing that surface compositions of Sr2 TiO3 F and Sr2 TiO3 with Ti 3+ and Ti 2+ species can be obtained on the reaction, respectively. We further highlight that a 'direct' reduction of the oxide precursor Sr2 TiO4 to Sr2 TiO3 is not possible using the same method. Therefore, the two-step modification of Sr2 TiO4 allows for the preparation of compounds with low oxidation states at the lowest temperatures used so far for hydride based reductions of titanium containing oxides (300 °C compared to ∼600 °C used previously). The observed differences in the reactivity of oxyfluorides compared to oxides are well supported by DFT based calculations of formation energies. They show that the formation of NaF is a strong driving force, resulting in exergonic reductions/hydride-fluoride substitution reactions as compared to the endergonic formation of Na2 O for pure oxide compounds.